Analisis Hukum Perampasan Aset Tindak Pidana Korupsi Dalam Konteks Keadilan dan Perlindungan Hak Asasi Manusia: Analisis Hukum Perampasan Aset Tindak Pidana Korupsi Dalam Konteks Keadilan dan Perlindungan Hak Asasi Manusia - Ainul Yaqin, Ach.; Ilham, Lailul; Yaqin, Ach. Ainul Yaqin; Lailul Ilham (Yapilin Press, 2025)
This research focuses on the legal analysis of asset confiscation resulting from corruption from the perspective of justice and human rights. Asset confiscation is seen as an important instrument in recovering state losses and strengthening the anti-corruption system, but its practice raises serious problems related to the protection of individual rights, especially those of well-intentioned third parties. The research method used is normative legal, emphasizing library research, analysis of laws and regulations, international legal instruments, and a review of relevant legal literature. The results indicate a tension between the state's interest in recovering losses from corruption and its obligation to safeguard the basic rights of citizens. Normatively, national regulations have regulated the mechanism for asset confiscation, but there are still implementation weaknesses, overlapping authority between institutions, and the absence of specific regulations regarding non-conviction-based asset forfeiture as stipulated in international standards. The implications of this research emphasize the importance of legal reform through the establishment of specific laws on asset recovery, institutional harmonization, and the adoption of international practices that uphold the principles of proportionality and substantive justice. Thus, asset confiscation policies can be more effective, accountable, and remain in line with human rights protection.